Microstructural characterization and mechanical properties of Al7075/BN metal matrix composites prepared by conventional casting method. (6th March 2019) - Vignesh Kumar, V; Raja, K; Chandrasekaran, K; Ramkumar, T
Abstract: The research article addresses to improve the mechanical behaviour of the Al 7075 composites like tensile, surface roughness (SR) and thrust force fabricated by conventional stir casting process with a modernized three step stirring method. Boron Nitride particles are reinforced with varying wt% of 3, 6 and 9 respectively. Boron Nitride particles are characterized using metallurgical microscopy (MM), Field Emission Scanning Electron Microscopy (FESEM) & Energy Dispersive x-ray Analysis (EDAX). The density and hardness of the samples are determined using Archimedes principle and micro hardness testing machine. Drilling experiments are conducted for the prepared composites. Fully carbide drill bit is used for the entire experiment with varying input parameters such as (Speed, Feed & Point of angle). The results reveal that the surface roughness is decreased due to the presence of hard ceramic phase. The tensile behaviour of the composites is increased when compared with the base material. Further the tensile fractography and drill worn surface is analyzed using SEM.